(untitled) (Acta Scientiarum. Education, 2015)
This article aims to discuss education as a social question in Carneiro Leão’s public instruction reform. Based on administrative reports and school programs published between 1923 and 1926, this text seeks to analyze the consolidation of instruments for social intervention in schools of Rio de Janeiro, pointing at possible connections between Carneiro Leão and the educational project of the Brazilian Association of Education.